Performance, Carcass Yield, Muscle Amino Acid Profile, and Levels of Brain Neurotransmitters in Aged Laying Hens Fed Diets Supplemented with Guanidinoacetic Acid - Omar A. Ahmed-Farid (MDPI AG, 2021)
Guanidinoacetic acid (GA) is a natural precursor of creatine in the body and is usually used to improve the feed conversion and cellular energy metabolism of broiler chickens. The objective was to elucidate the effect of dietary supplementation of GA on carcass yield, muscle amino acid profile, and concentrations of brain neurotransmitters in laying hens. In total, 128 72-week-old ISA Brown laying hens were assigned to four equal groups (32 birds, eight replicates per group). The control group (T1) was fed a basal diet with no supplements, while the other experimental groups were fed a basal diet supplemented with 0.5 (T2), 1.0 (T3), and 1.5 (T4) g GA kg−1 diet. The T3 and T4 groups showed higher hen-day egg production and carcass yield compared to the control group (p = 0.016 and 0.039, respectively). The serum creatine level increased linearly with the increased level of dietary GA (p = 0.007). Among the essential amino acids of breast muscle, a GA-supplemented diet linearly increased the levels of leucine, isoleucine, phenylalanine, methionine, and threonine in the breast (p = 0.003, 0.047, 0.001, 0.001, and 0.015, respectively) and thigh (p = 0.026, 0.001, 0.020, 0.009, and 0.028, respectively) muscles. GA supplementation linearly reduced the level of brain serotonin compared to the control group (p = 0.010). Furthermore, supplementation of GA in the diet of laying hens linearly increased the level of brain dopamine (p = 0.011), but reduced the level of brain Gamma-aminobutyric acid (p = 0.027). Meanwhile, the concentration of brain nitric oxide did not differ between the experimental groups (p = 0.080). In conclusion, the dietary supplementation of GA may improve the carcass yield and levels of essential amino acids in the breast muscles, as well as the brain neurotransmitters in aged laying hens.